Efficacy of chemomechanical caries removal in reducing cariogenic microbiota: a randomized clinical trial - Michelle Mikhael AMMARI; Luiz Flávio Martins MOLITERNO; Raphael HIRATA JÚNIOR; Mariana Canano SÉLLOS; Vera Mendes SOVIERO; Wagner Pereira COUTINHO FILHO (Sociedade Brasileira de Pesquisa Odontológica, 2014)
The aim of this study was to compare the efficacy of chemochemical methods (Carisolv™ and Papacárie®) versus the manual method (excavators) in reducing the cariogenic microbiota in dentine caries of primary teeth. Forty-six healthy children (5 to 9 years old) having at least one primary tooth with a cavitated dentine carious lesion were included in the study. The teeth presented no clinical or radiographic signs of pulpal involvement. The sample of 74 teeth was randomly divided into three different groups: Papacárie® (n = 25), Carisolv™ (n = 27) and Manual (n = 22). Samples of carious and sound dentine were collected with sterile excavators before and after caries removal in the three groups. The dentine samples were transferred to glass tubes containing a 1mL thioglycollate medium used as a carrier and enriched for microbiological detection of mutans streptococci and Lactobacillus spp, after incubation for 6h at room temperature. The minimum detection value for colony forming units (CFU) was 3.3 x 102 CFU/ml, and the results were converted into scores from 0 to 4. A significant difference was observed in relation to the microbiological scores before and after caries removal for all methods (Wilcoxon test; p < 0.001). The use of chemomechanical methods for caries removal did not improve the reduction of cariogenic microorganisms in dentine caries lesions, in comparison with manual excavation.